PERANCANGAN ALAT ANGKUT KASUR DENGAN MENGGUNAKAN METODE REVERSE ENGINEERING DAN VDI 2221 (STUDI KASUS: PT. XYZ) - Gosal, Marchelino; Daywin, Frans Jusuf; Adianto (Jurnal Mitra Teknik Industri, 2023)
At this time material handling in the industry is still done manually which can be interpreted as the task of moving goods, material flow, final products or other objects that use humans as a source of energy. At PT. XYZ activities related to lifting and also moving goods carried out were manually moving springbeds but workers found it difficult and also had several complaints and pain in parts of the body based on the Nordic Body Map questionnaire given to workers. Therefore the authors created a design for a springbed conveyance to move mattresses from the production floor to the warehouse in accordance with the principles of ergonomic operators using the Reverse Engineering method to develop products that function to improve the performance of workers and a conveyance. And also use the VDI 2221 method to optimize the technology, material and economic conditions of the conveyance. The results of the REBA analysis of the two jobs carried out by workershave a high level of risk with a REBA score of 8 for lifting and a very high risk level with a REBA score of 12 for laying. 4,662. The Lifting Index (LI) value obtained is> 1 so that it has a risk of injury to the operator.